Senp2 regulates adipose lipid storage by de-SUMOylation of Setdb1. (14th February 2018) - Zheng, Quan; Cao, Ying; Chen, Yalan; Wang, Jiqiu; Fan, Qiuju; Huang, Xian; Wang, Yiping; Wang, Tianshi; Wang, Xiuzhi; Ma, Jiao; Cheng, Jinke
Abstract: One major function of adipocytes is to store excess energy in the form of triglycerides. Insufficient adipose lipid storage is associated with many pathological conditions including hyperlipidemia, insulin resistance, and type 2 diabetes. In this study, we observed the overexpression of SUMO-specific protease 2 (Senp2) in adipose tissues during obesity. Adipocyte Senp2 deficiency resulted in less adipose lipid storage accompanied by an ectopic fat accumulation and insulin resistance under high-fat diet feeding. We further found that SET domain bifurcated 1 (Setdb1) was a SUMOylated protein and that SUMOylation promoted Setdb1 occupancy on the promoter locus of Pparg and Cebpa genes to suppress their expressions by H3K9me3. Senp2 could suppress Setdb1 function by de-SUMOylation. In adipocyte Senp2 -deficiency mice, accumulation of the SUMOylated Setdb1 suppressed the expression of Pparg and Cebpa genes as well as lipid metabolism-related target genes, which would decrease the ability of lipid storage in adipocytes. These results revealed the crucial role of Senp2–Setdb1 axis in controlling adipose lipid storage.